Faktor-Faktor yang Mempengaruhi Kinerja Dosen - Arisal Arisal (JURNAL MAPPESONA, 2023)
This article aims to obtain an overview of the lecturer's performance and the factors that influence it.  Lecturer performance is the activity of a lecturer carrying out his work or performance.  The performance of lecturers can be seen from their enthusiasm in carrying out the duties of the tridarma of higher education imposed on them. The factors that affect lecturer performance are 1) Lecturer competence, which consists of paedagogic, professional, social and personality competencies.   2) Job satisfaction is an employee's attitude towards work related to work situations, cooperation between employees, benefits received at work, and matters concerning physical and psychological factors.  3) The lecturer's attitude is a lecturer's response or judgment that can be like or dislike, accept or reject, and positive or negative towards an object. The lecturer's attitude consists of three components, affective yaiyu, cognition, and conation.  4) The lecturer's personality is a complete combination of attitudes, traits, mindsets, emotions, and also values that influence the lecturer to do something right in accordance with his environment.  5) Lecturer motivation is the encouragement of a lecturer both from within and outside the lecturer who can move the lecturer to be able to work as well as possible to achieve organizational goals.  And 6) Organizational culture is a system of shared meanings shared by members that distinguishes an organization from other organizations.